Tire tread
By integrating a tread pattern with a long total index of 17 or less and a specialized rubber composition in winter tires, the challenges of achieving high wet braking and snow traction are addressed, resulting in enhanced safety and performance.
Patent Information
- Application Number
- JP2024558972
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-04
- Filing Date
- 2023-04-04
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-04-04
AI Technical Summary
Winter tires face a challenge in achieving high wet braking performance without compromising grip on snow and ice, as traditional solutions that improve wet braking often lead to reduced winter traction.
A combination of a specific tread pattern with a long total index (As) of 17 or less and a rubber composition containing modified styrene butadiene copolymer rubber, silica, hydrocarbon resin, and octyl oleate, which enhances both wet braking and snow traction performance.
The proposed solution effectively improves wet braking performance while maintaining excellent grip on snow and ice, meeting the safety requirements for winter tires.
Smart Images

Figure 2025511363000006 
Figure 2025511363000001 
Figure 2025511363000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a tire tread and to a winter tire equipped with such a tread. In particular, but not exclusively, the invention is advantageous for passenger car tires (PSR tires). In the following description, explicit reference is made to passenger car tires without loss of generality. [Background technology]
[0002] Winter tyres must fulfil safety requirements regarding the grip of the tyre, i.e. grip on ice and snow.
[0003] In order to ensure safer vehicle operation in winter weather, winter tires should also ensure high performance in wet braking. Generally, it is difficult to meet such requirements, since solutions that improve wet braking also lead to a deterioration of road grip in winter. Summary of the Invention [Problem to be solved by the invention]
[0004] The combination of properties of a tire tread can be achieved by adjusting the design characteristics of the tread pattern and the composition of the rubber that forms the tread pattern: the synergistic effect of both technologies allows the tire to meet the expected requirements.
[0005] Typically, the rubber composition used in the tread of a winter tire needs to remain soft even in low temperature conditions. A softer tire can grip icy or snowy surfaces more efficiently, improving grip and handling. Unlike summer tires, which harden quickly at low temperatures, winter tires perform best when temperatures are below 7°C.
[0006] Traditionally, rubber compositions used in winter tire treads contain natural rubber (NR) and polybutadiene rubber (BR) as the main synthetic components of the rubber blend. Natural rubber provides softness to the composition, while polybutadiene rubber is known to provide the necessary grip level at temperatures below 7°C due to its inherently low glass transition temperature (Tg).
[0007] Alternatively, increasing the amount of silica and / or solution polymerized styrene butadiene rubber (S-SBR) in the tread rubber composition significantly improves wet braking performance, but at the same time reduces grip performance on snow or ice.
[0008] Winter tires have tread patterns with features designed to optimize winter performance, such as the depth of the tread grooves, which provide cavities for snow and enhanced grip, as well as the number, shape and placement of sipes within the tread blocks.
[0009] Hereinafter, the term "rib" refers to the raised portions of the tread pattern spaced apart by grooves and made up of tread blocks.
[0010] Hereinafter, the term "groove" refers to a channel extending longitudinally and axially along the tire and providing a space between two adjacent tread ribs or between two adjacent tread blocks having a width greater than 2 mm and a depth along the radial direction of the tire of at least 50% of the tread depth.
[0011] Hereinafter, "tread depth" refers to the distance from the surface of the tread to the bottom of the deepest groove.
[0012] Hereinafter, "longitudinal direction" refers to the direction of rotation of the tire, which is conventionally identified as the direction along the y-axis in a Cartesian coordinate system.
[0013] Hereinafter, "axial" refers to a direction perpendicular to the longitudinal direction and extending transversely to the direction of rotation of the tire, and is conventionally identified as being along the x-axis in a Cartesian coordinate system.
[0014] Hereinafter, "radial" refers to directions along the radius of the tire, i.e., through the tire's axis of rotation and substantially perpendicular to said direction, and is conventionally identified as being along the z-axis in a Cartesian coordinate system.
[0015] Hereinafter, "tread block" means a raised portion of rubber bounded by edges that contacts the road surface and provides traction.
[0016] Hereinafter, "sipe" refers to any small, narrow cut in the tread blocks, having the shape of an element that repeats periodically along the axial and / or longitudinal direction of the tire, having at least two end points, a maximum width of 1 mm, and suitable for improving traction and preventing skidding.
[0017] Hereinafter, the term "sipe element" refers to any of the periodically repeated straight lines that make up a sipe.
[0018] Hereinafter, "slot" refers to any narrow cut molded into a tire tread block having at least two endpoints, a width greater than 1 mm and not greater than 2 mm, and a depth not greater than 50% of the tread depth.
[0019] Hereinafter, "block edge" refers to that portion of a tread block adjacent a slot or groove.
[0020] Sipes in winter tread patterns are known to improve tire traction and reduce braking distances. In normal conditions, sipes make the tire tread more flexible, improving the tire's ability to push into small changes in the road surface, enhancing contact and grip with the road surface. In wet conditions, sipes improve wet grip by draining water from the contact area between the tire and the road surface, breaking the water film and preventing hydroplaning. In winter conditions, sipes increase traction by opening the slits as the tread is pushed against the road surface and trapping snow inside. Typically, the shape and configuration of sipes and block edges are intended to balance the pattern stiffness to provide high performance in both winter and wet traction.
[0021] Therefore, there is a need to find a winter tread solution that combines composition and pattern characteristics that provide high wet traction performance while maintaining good winter performance on snow and ice. [Means for solving the problem]
[0022] The inventors have devised a solution capable of meeting the aforementioned needs, resulting in a significant improvement in both wet braking and grip on snow and ice. In particular, the invention is based on the combination of a specific tread pattern and a specific composition that constitutes the tread itself.
[0023] A first aspect of the present invention is a tire tread having a tread pattern with a long total index (As) of 17 or less, the tread being composed of a rubber composition including: (a) a crosslinkable unsaturated chain polymer base containing 10 to 50 phr of a modified styrene-butadiene copolymer rubber having a glass transition temperature (Tg) of -50°C or less measured by differential scanning calorimetry; (b) a filler containing 40 to 100 phr of silica; (c) a plasticizer system containing a hydrocarbon resin and 8 to 25 phr of octyl oleate; and (d) a vulcanization system, the hydrocarbon resin having a softening point of 110 to 145°C, preferably 110 to 128°C, and an average molecular weight of 700 to 1500 g / mol.
[0024] A second aspect of the invention is a winter tyre comprising a tread according to the first aspect.
[0025] Preferred features of the invention are the subject of the dependent claims. [Brief description of the drawings]
[0026] [Figure 1] FIG. 1 is a diagram illustrating an example of a detail of a front view of a tread (1). The tread (1) includes tread blocks (4) with each block edge (5) adjacent a groove (2) or slot (3), the tread blocks (4) including sipes (6), each sipe formed of a plurality of sipe elements (7). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Hereinafter, the term "crosslinkable unsaturated chain polymer base" refers to any natural or synthetic non-crosslinked polymer that is capable of assuming all the chemical, physical and mechanical properties typically exhibited by elastomers after crosslinking (vulcanization) with a sulfur system.
[0028] Hereinafter, a vulcanization system refers to a complex of components, including a curative, such as sulfur, and an accelerator, that is added at the final mixing stage in the preparation of a composition and whose purpose is to promote the vulcanization of the polymer base after the composition has been exposed to vulcanization temperatures.
[0029] Hereinafter, the "Long Total Index (As)" is the sum of the projections of the sipes (6) and block edges (5) in the axial direction of the tire, taking into account each element (7) when the sipes (6) or block edges (5) are created, divided by the circumference of the tire, and is calculated by the following formula:
[0030]
number
[0031] Ls (cosθs) is the orthogonal projection of each element (7) constituting the sipe (6) or block edge (5) in the axial direction of the tire.
[0032] The larger the long total index (As), the greater the number of sipes (6) and block edges (5) that are generally axially oriented, and the smaller the long total index, the fewer the number of sipes (6) and block edges (5) that are generally axially oriented.
[0033] Preferably, the aforesaid tread pattern has a long total index (As) of 15 or less.
[0034] More preferably, said tread pattern has a long total index (As) of 13 or less.
[0035] The rubber composition according to the present invention contains 10 to 50 phr of a modified styrene-butadiene copolymer rubber having a glass transition temperature (Tg) of -50°C or lower. Preferred examples of the modified styrene-butadiene copolymer rubber are described in EP3372639A1 (paragraphs
[0027] to
[0065] ), which are incorporated herein by reference. Preferably, the modified styrene-butadiene copolymer is contained in the rubber composition in an amount of 20 to 40 phr, more preferably 20 to 30 phr.
[0036] The rubber composition according to the present invention includes a hydrocarbon resin. In an embodiment, the softening point of the hydrocarbon resin is 110° C. or more, preferably 115° C. or more, preferably 118° C. or more. From the viewpoint of suppressing an increase in tan δ at 0° C., the softening point of the hydrocarbon resin is preferably 145° C. or less. For example, the softening point can be 143° C. or less, 140° C. or less, 136° C. or less, 135° C. or less, 133° C. or less, or 130° C. or less. From the viewpoint of compatibility of the resin with the rubber component, the weight average molecular weight of the hydrocarbon resin is generally in the range of 700 to 1500 g / mol. The weight average molecular weight is determined by gel permeation chromatography (GPC) against a polystyrene standard.
[0037] In some embodiments, the weight average molecular weight of the resin can be 800 g / mol or more, preferably 900 g / mol or more, and more preferably 1000 g / mol or more. In other embodiments, the weight average molecular weight of the hydrocarbon resin can be 1400 g / mol or less, preferably 1300 g / mol or less, and more preferably 1200 g / mol or less.
[0038] In one embodiment, the hydrocarbon resin has a softening point above 100° C. and a weight average molecular weight of 700 to 1500 g / mol. More preferably, the hydrocarbon resin is a fully hydrogenated C9 resin with a softening point above 100° C. and a weight average molecular weight of 700 to 1500 g / mol.
[0039] The hydrocarbon resin is one produced by subjecting the resin to substantially complete (e.g., complete) reductive hydrogenation. The resin used as the starting material is selected from C5 resins, C5 / C9 resins, C9 resins, and combinations thereof.
[0040] Examples of C5 resins that can be used to produce fully hydrogenated C5 resins include aliphatic petroleum resins obtained by (co)polymerizing C5 fractions obtained by thermal cracking of naphtha in the petrochemical industry. C5 fractions usually contain olefinic hydrocarbons such as 1-pentene, 2-pentene, 2-methyl-1-butene, 2-methyl-2-butene, and 3-methyl-1-butene, and diolefinic hydrocarbons such as 2-methyl-1,3-butadiene, 1,2-pentadiene, 1,3-pentadiene, and 3-methyl-1,2-butadiene. They may also contain other monomers, such as DCPD. Any commercially available product can be used as the C5 resin.
[0041] "C5 / C9 resin" refers to a C5-C9 synthetic petroleum resin, examples of which include solid polymers obtained by polymerization using petroleum-derived C5-C11 fractions containing AlCl3 and Friedel-Crafts catalysts such as BF3, and more specific examples include copolymers mainly composed of styrene, vinyltoluene, α-methylstyrene, indene, etc. From the viewpoint of compatibility with rubber components, resins containing a small amount of C9 or higher components are preferred as C5 / C9 resins. For example, the amount of C9 or higher components can be less than 50% by weight, preferably less than 40% by weight, based on the total amount of the resin. Any commercially available product can be used as the C5 / C9 resin.
[0042] "C9 resin" refers to a C9 synthetic petroleum resin, and examples of such resins include polymers obtained by polymerization using a Friedel-Crafts catalyst such as AlCl3 or BF3. Examples of C9 resins include copolymers mainly composed of indene, styrene, α-methylstyrene, vinyltoluene, etc. Any commercially available product can be used as the C9 resin. For example, the resin has a softening point of about 118 to 128°C, a weight average molecular weight (Mw) of about 1100 g / mol, and a glass transition temperature (Tg) of about 65 to 75°C.
[0043] The glass transition temperature (Tg) of the hydrocarbon resins and modified styrene butadiene copolymers is measured by differential scanning calorimetry (DSC). The Tg values reported herein are measured using DSC with an onset temperature of -140°C and a heating rate of 15°C / min. Unless otherwise specified, all test methods described herein are performed at a temperature of 23°C and a relative humidity of 50%.
[0044] As used herein, "fully hydrogenated" means that the resin component contains less than 5% olefinic protons. In some embodiments, the fully hydrogenated resin may contain less than 4%, preferably less than 3%, more preferably less than 2%, such as less than 1%, less than 0.5%, or less than 0.1%, such as less than 0.05% olefinic protons. In one embodiment, the fully hydrogenated resin may contain 0 to about 3% olefinic protons, i.e., about 97 to 100% hydrogenated. In one embodiment, the fully hydrogenated resin may contain 0 to about 2% olefinic protons, i.e., about 98 to 100% hydrogenated. In one embodiment, the fully hydrogenated resin may contain 0 to about 1% olefinic protons, i.e., about 99 to 100% hydrogenated. In one embodiment, the fully hydrogenated resin may contain about 0% olefinic protons. In a preferred embodiment, the hydrocarbon resin is included in the rubber composition in an amount ranging from 2 to 15 phr, more preferably from 5 to 10 phr.
[0045] The rubber composition of the present invention contains silica as a filler. The rubber composition described herein may use any known silica filler or a combination of different types of silica. The silica may be selected according to its specific surface area. The average specific surface area of the silica may be determined by N2 adsorption, i.e. NSA (nitrogen surface area), measured according to the Brunauer-Emmett-Teller (BET) method, and by the Cetyltrimethylammonium bromide (CTAB) adsorption method. The CTAB specific surface area is the external surface. The Brunauer-Emmett-Teller (BET) method is described in the Journal of the American Chemical Society, Vol. 60, p. 309, published in February 1938, and conforms to the standard NF ISO 5794-1, Appendix D (June 2010). The Cetyltrimethylammonium bromide (CTAB) adsorption method conforms to ASTM D6845. The silica used in the present invention has a specific surface area of 105 to 145 m 2 The silica used in the present invention may have a CTAB specific surface area of 100 to 130 m 2 The silica may be blended in the rubber composition according to the present invention in an amount ranging from 40 to 100 phr, preferably from 50 to 90 phr, and more preferably from 60 to 80 phr.
[0046] In a preferred embodiment, the rubber composition further contains a silane coupling agent. The silane coupling agent is used to increase the compatibility of the crosslinkable polymer base with the silica. Any silane coupling agent known to a person skilled in the art can be used in the rubber composition. In a preferred embodiment, the silane coupling agent used in the rubber composition is bis(triethoxysilylpropyl) disulfide (Si 75). The silane coupling agent can be introduced into the rubber composition in an amount ranging from 3 to 10 phr.
[0047] In a preferred embodiment, the filler contained in the rubber composition is not only silica but also carbon black, which may be introduced into the composition in an amount ranging from 3 to 20 phr, more preferably from 5 to 15 phr, and more preferably from 8 to 12 phr.
[0048] The rubber composition of the present invention further comprises octyl oleate in the plasticizer system, which is introduced into the composition according to the present invention in an amount of 8 to 25 phr, more preferably 10 to 20 phr.
[0049] In a preferred embodiment, the crosslinkable polymer base comprises natural rubber (NR) and polybutadiene rubber (BR). The natural rubber is contained in the rubber composition in an amount of 40 to 60 phr, preferably 45 to 55 phr, and the polybutadiene rubber is contained in the rubber composition in an amount of 15 to 50 phr, more preferably 20 to 30 phr.
[0050] Preferably, the crosslinkable unsaturated chain polymer base contains 20 to 30 phr of modified styrene-butadiene copolymer rubber having a glass transition temperature (Tg) of −50° C. or lower, 45 to 55 phr of natural rubber, and 20 to 30 phr of polybutadiene rubber.
[0051] In a preferred embodiment, the tread that is the subject of the present invention is used in passenger vehicle tires.
[0052] A second aspect of the invention is a winter tyre comprising a tread according to the first aspect. EXAMPLES
[0053] The following examples, with reference to FIG. 1 showing three different tread patterns, are intended to illustrate and explain the invention for a better understanding, but are not intended to limit the invention.
[0054] Four compositions (A-D) were prepared. The first composition (A) is a comparative composition, while the other three compositions (B-D) are compositions according to the invention. The four compositions were then subjected to a series of tests to evaluate their adhesion under wet and winter conditions. In particular, for each composition, the value of TanD at 0°C and the value of E' at -20°C were measured, which are indicators of wet winter braking performance and grip index, respectively.
[0055] The example compositions were obtained according to the following procedures.
[0056] -Preparation of Composition- (First Mixing Stage) All materials except the vulcanization system were added to a tangential mixer with an internal volume of 230-270 liters before mixing began. The filling rate reached 66-72%.
[0057] The mixer was operated at a speed of 40-60 rpm, and the mixture was removed when it reached a temperature of 140-160°C.
[0058] (Second Mixing Stage) The mixture obtained in the previous step was mixed again in the mixer at a speed of 40 to 60 rpm, and then, when the temperature reached 130 to 150°C, the mixture was taken out.
[0059] (Third Mixing Stage) The vulcanization system was added to the mixture obtained in the previous step. The filling rate reached 63-67%.
[0060] The mixer was operated at a speed of 20 to 40 rpm, and when the mixture reached a temperature of 100 to 110°C, the mixture was removed.
[0061] Table I shows four rubber compositions A to D.
[0062] [Table 1]
[0063] Natural rubber is a naturally occurring 1,4-cis-polyisoprene rubber.
[0064] Polybutadiene rubber is a polymer base made of polybutadiene.
[0065] The modified styrene butadiene rubber was prepared by the following procedure. A cyclohexane solution of 1,3-butadiene and a cyclohexane solution of styrene were poured into a dry, nitrogen-purged pressure-resistant glass container (800 mL) so that the 1,3-butadiene monomer was 67.5 g and the styrene was 7.5 g. 0.6 mmol of 2,2-di(tetrahydrofuryl)propane and 0.8 mmol of n-butyllithium were added to the mixture, and polymerization was carried out at 50°C for 1.5 hours. At this point, the polymerization conversion rate was almost 100%. To the polymerization reaction system, 0.72 mmol of a modifier was added, and a modification reaction was carried out at 50°C for 30 minutes. Thereafter, 2 mL of 5% by mass of 2,6-di-t-butyl-p-cresol (BHT) in isopropanol was added to stop the reaction, and the mixture was dried in a normal manner to obtain a modified styrene butadiene rubber. The microstructure of the resulting modified styrene butadiene rubber was measured, and as a result, the bound styrene content was 10% by mass, the vinyl content of the butadiene portion was 40%, and the peak molecular weight was 200,000.
[0066] The silica used is sold by Evonik under the trade name "ULTRASIL5500 GR".
[0067] The carbon black is a carbon black classified as N234 or N330.
[0068] The silane coupling agent used was Si75 sold by Evonik.
[0069] Octyl oleate is sold under the trade name "Permavis T" by Traquisa.
[0070] MES oil is sold by Nynas under the trade name "Nytex 832."
[0071] The hydrocarbon resin used is a fully hydrogenated C9 resin.
[0072] Aromatic C9 resin is sold by Rain Carbon under the trade name "Novares TD100."
[0073] As is clear from Table I, the compositions of the present invention differ from the compositions of the comparative examples in that (i) a modified styrene-butadiene rubber is used in the polymer base, (ii) the amounts of silica and octyl oleate used are large, and (iii) a hydrocarbon resin is used in the plasticizer system.
[0074] As described above, the Tan D value at 0° C. and the E′ value at −20° C. were measured for each of the compositions A to D (in accordance with the ASTM D5992 standard).
[0075] Table II shows the results of the tests performed.
[0076] [Table 2]
[0077] The four compositions A to D were tested in three different tread patterns (patterns 1 to 3).
[0078] Patterns 1 to 3 are shown in Figure 1. In particular, patterns 1 and 2 are outside the scope of the present invention, and have long total indices of 22.2 and 19.8, respectively. Pattern 3 is an example of the present invention, and has a long total index of 11.5.
[0079] Each of the three patterns was created by alternating each of the four rubber compositions of Table I.
[0080] Twelve treads with three patterns and four rubber compositions were tested from the perspective of wet braking. Wet braking performance is determined by the braking distance from 80km / h on a wet road surface. Specifically, the braking distance from 80km / h to 20km / h is measured.
[0081] Table III shows the wet braking test values: To more clearly show the advantages of the compositions according to the invention, the values in Table III are given as indices for the combination of Pattern 1 and Composition A.
[0082] [Table 3]
[0083] In addition, snow traction tests were conducted on six treads made with patterns 1 to 3 using compositions A and C. Snow traction performance was measured as the time (in seconds) it took to accelerate from 5 to 35 kilometers per hour on a snowy road.
[0084] Snow traction: The time it takes to accelerate from 5 to 35 kilometers per hour.
[0085] Table IV shows the snow traction values. To more clearly show the advantages of the compositions according to the invention, the values in Table IV are expressed as an index for the combination of Pattern 1 and Composition A. The higher the value, the better the traction performance on snow.
[0086] [Table 4]
[0087] As can be seen from the values given in Tables III and IV, the tread obtained according to the invention, i.e. by combining pattern 3 with composition B or composition D, guarantees an improvement in wet braking properties while at the same time providing the highest level of traction on snow.
[0088] In summary, the inventors have discovered that when a tread is made of a rubber compound having a specific composition in terms of polymer base, silica amount and plasticizer system, a tread having a tread pattern with a long total index (As) of 17 or less can meet the safety requirements for wet grip performance of a winter tread.
Claims
1. A tire tread having a tread pattern with a long total index (As) of 17 or less, the tread being composed of a rubber composition including: (a) a crosslinkable unsaturated chain polymer base containing 10 to 50 phr of a modified styrene-butadiene copolymer rubber having a glass transition temperature (Tg) of -50°C or less as measured by differential scanning calorimetry; (b) a filler containing 40 to 100 phr of silica; (c) a plasticizer system containing a hydrocarbon resin and 8 to 25 phr of octyl oleate; and (d) a vulcanization system, the hydrocarbon resin having a softening point of 110°C or more and an average molecular weight of 700 to 1500 g / mol.
2. 2. Tire tread according to claim 1, wherein said tread pattern has a long total index (As) equal to or less than 15, preferably less than 13.
3. 3. Tire tread according to claim 1 or 2, wherein said crosslinkable unsaturated chain polymer base further comprises 15 to 50 phr of polybutadiene rubber (BR) and 40 to 60 phr of natural rubber (NR).
4. Tire tread according to any one of the preceding claims, wherein said plasticizer system comprises from 2 to 15 phr of a hydrocarbon resin having a softening point between 118 and 128°C and an average molecular weight between 700 and 1500 g / mol.
5. The silica has a CTAB value of 100 to 130 m 2 / g and NSA value is 105 to 145m 2 / g, the CTAB value being measured according to ASMT D6845 and the NSA value being measured by the Brunauer-Emmett-Teller (BET) method.
6. A tire tread according to any one of the preceding claims, wherein said hydrocarbon resin has a glass transition temperature (Tg) measured by differential scanning calorimetry of 65 to 75°C.
7. Tyre tread according to any one of the preceding claims, wherein said hydrocarbon resin has an olefinic proton content of less than 5%.
8. The tire tread according to any one of claims 1 to 7, wherein the crosslinkable unsaturated chain polymer base comprises 20 to 40 phr, preferably 20 to 30 phr, modified styrene butadiene copolymer rubber having a glass transition temperature (Tg) of -50°C or less, 45 to 55 phr of natural rubber (NR), and 20 to 30 phr of polybutadiene rubber (BR).
9. A tire tread according to any one of claims 1 to 8, wherein said fillers comprise carbon black and from 60 to 80 phr silica.
10. Tire tread according to any one of the preceding claims, wherein said plasticizer system comprises from 5 to 10 phr of a hydrocarbon resin and from 10 to 20 phr of octyl oleate.
11. Tyre tread according to any one of the preceding claims, wherein the rubber composition further comprises a silane coupling agent, preferably Si75.
12. A tire tread according to any one of claims 1 to 11, for use in passenger car tires.
13. A winter tire comprising a tread according to any one of the preceding claims.
Citation Information
Patent Citations
Tire
JP2009263587A
tire
JP2020059807A
Rubber composition and tire
WO2017077714A1